New insights on lithium-cation microsolvation by solvents forming hydrogen-bonds: water versus methanol - Llanio-Trujillo, J. L. (2013)
This investigation uses a recent methodology, essentially based on our evolutionary algorithm (EA) to get new insights about the energetics and structure of the first solvation shells of lithium ion in polar solvents that form important hydrogen bonds. We employed the EA to search for the low-energy structures of the Li+(H2O)n and Li+(CH3OH)n clusters (with n ⩽ 20) as modeled by commonly used rigid nonpolarizable force-field potentials. Particular emphasis is given to the characterization of the putative global minima; for Li+(H2O)17, the EA discovered a new global minimum with five water molecules directly coordinating the ion. Smaller-size clusters were, then, re-optimized by employing electronicstructure methods, namely, DFT (with the B3LYP functional and both the 6-31+G∗ and 6-311+G∗∗ basis sets) and MP2 (with the aug-cc-pVDZ basis set). In the case of Li+(H2O)n, the ab initio global minimum structures are similar to those obtained with the EA up to n = 10. However, for n = 17, the structure of the global minimum discovered by the EA is different from the lowest-energy cluster obtained after re-optimization at the MP2/aug-cc-pVDZ level of theory. Such energy reorder may be attributed to the water–water interaction. As for the Li+(CH3OH)n clusters, the re-optimization process leads more often to a reorder in the energy of the minimum structures. Thus, forfluxional clusters like the Li+(CH3OH)n ones that show a huge number of stationary configurations within a small energy window, it is mandatory to carefully choose various structures, besides the global minimum, to be re-optimized at the ab initio or DFT levels. Due to the difficulty on choosing adequate departing structures by the usually employed chemical intuition, we noticed that some low-energy minima (including the global one) of even small Li+(CH3OH)n clusters were missed in literature. We showcase this problem in the Li+(CH3OH)6 cluster, whose vibrational frequencies in the C–O stretching region and corresponding infrared intensities were calculated at the DFT level of theory and compared with previously reported results.